Calidad microbiológica de la carne de pollo expendida en el Mercado Mayorista Miguel Grau del distrito de Tacna: Microbiological quality of chicken meat sold in the Miguel Grau Wholesale Market in the Tacna district - Nina Inchuña, Mónica Santamaría (2023)
Material and methods: The sample size consisted of 75 samples, the provisions of the Peruvian Health Standard that establishes the Microbiological Quality Criteria of Health Quality and Safety for foods and beverages for Human Consumption were considered (Technical Health Standard No. 071 – MINSA/DIGESA-V.01) of 2008, applying to each sample the Standard Plate Count method of mesophilic aerobes, according to the methodology of the International Commission on Microbiological Specifications in Foods (ICMSF); Likewise, the investigation of Salmonella spp, under the AOAC 2014.01 method. PetrifilmTM Salmonella Express System.Results: It was determined, with the Standard Plate Count method, that 17,33 % of the samples exceeded the permissible limit referring to mesophilic aerobes.Regarding the investigation of Salmonella spp, the PetrifilmTM System allowed confirming its presence in 14,67 % of the total samples analyzed.Conclusion: It was concluded that the microbiological quality of 23 samples represented by 30,67 % do not meet the microbiological criteria established in current Peruvian regulations and are considered not suitable for human consumption.